2020
DOI: 10.3390/md18110534
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cytotoxic Effects on Tumor Cells of Exopolysaccharides from Tetraselmis suecica (Kylin) Butcher Grown Under Autotrophic and Heterotrophic Conditions

Abstract: Marine microalgae produce extracellular metabolites such as exopolysaccharides (EPS) with potentially beneficial biological applications to human health, especially antioxidant and antitumor properties, which can be increased with changes in crop trophic conditions. This study aimed to develop the autotrophic and heterotrophic culture of Tetraselmis suecica (Kylin) Butcher in order to increase EPS production and to characterize its antioxidant activity and cytotoxic effects on tumor cells. The adaptation of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 87 publications
0
15
1
Order By: Relevance
“…The study of Li [ 45 ] showed that low concentrations of polysaccharides could promote cell proliferation, and high concentrations could inhibit cell proliferation. Several studies have also shown that high concentrations of polysaccharides could inhibit the proliferation of tumor cells, and induce apoptosis [ 46 , 47 ]. They inferred that AP or SAP produce cytotoxic effects on cells with increasing concentrations, and this can lead to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Li [ 45 ] showed that low concentrations of polysaccharides could promote cell proliferation, and high concentrations could inhibit cell proliferation. Several studies have also shown that high concentrations of polysaccharides could inhibit the proliferation of tumor cells, and induce apoptosis [ 46 , 47 ]. They inferred that AP or SAP produce cytotoxic effects on cells with increasing concentrations, and this can lead to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Saxitoxins from T. erythraeum were also connected to mortality events in farmed pearl oysters (Negri et al ., 2004 ). Some of these cytotoxic activities may prove beneficial, for example, in the development and antitumor therapeutants; however, they will make commercial adoption of microalgae more complex (Parra‐Riofrío et al ., 2020 ).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…7b). A fundamental role in EPS production is played by variation in salinity, which exerts oxidative stress on cells and affects cellular ion balance (Guzman-Murillo and Ascencio 2001;Parra-Riofrío et al 2020). At lower salinity, cellular ion concentrations increased and their ion ratios were constant, whereas at salinity higher than 20, ion ratios became variable (Kirst 1990), affecting the amount of EPS production in T. suecica and its adaptation mechanisms to osmotic stress (Guzman-Murillo and Ascencio 2001).…”
Section: Discussionmentioning
confidence: 99%